(1104) System of Indicators of Economic Efficiency of Social Production used in Practice of the USSR Planning نظام مؤشرات الكفاءة الاقتصادية للإنتاج الاجتماعي المستخدم في تخطيط الاتحاد السوفيتى - G. Galakhov. (INP., 2018)
Determination of economic efficiency of planned decisions adopted is a fundamental problem of planning at the present stage of development. Data on economic efficiency provide possibilities of measuring ratios of expenditures to results and selecting the most rational ways of national economic development.